Comparison of sulfamethoxazole (SMX) degradation effect under different experimental conditions. Issue 1 (1st November 2022) - Cheng, Fangfang; Yang, Yina; Xu, Su; Wang, Chao; Liu, Han; Liao, Wenchao
Abstract : Sulfonamides are an important class of synthetic antibacterial medications that is widely utilized and pollute many water bodies. In this study, sulfamethoxazole was selected as the representative of sulfa antibiotics. A molybdenum disulfide-based catalyst was synthesized by hydrothermal method and used to activate peroxymonosulfate (PMS) for the degradation of sulfamethoxazole in water. Co@MoS2 was characterized by scanning electron microscope (SEM) and X-ray diffraction (XRD). The experimental conditions, Cobalt ion concentration, and light effect have been investigated. High-Performance Liquid Chromatography (HPLC) was used to measure the concentration of sulfamethoxazole. The results showed that the Co@MoS2 /PMS experimental conditions could effectively degrade sulfamethoxazole wastewater.